Pemanfaatan Media Digital dalam Pelatihan Aplikasi ChemDraw - Muh. Arwin; Haris Munandar; Erga Kurniawati; Thayban Thayban; Sufriyanto Ibrahim (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Mastery of the ChemDraw application is an important skill for chemistry students in supporting academic activities, especially in drawing chemical structures and reactions. However, not all students have the opportunity to learn this application formally. This service activity aims to provide training in the use of ChemDraw online to chemistry students by utilizing digital media. The implementation method includes an interactive workshop approach through Zoom, Google Meet, and social media as a means of disseminating information and documentation. The results showed that the training was effective in improving participants' understanding and skills in using ChemDraw. Digital media proved to be an efficient and flexible tool for training computer-based applications. This activity supports the improvement of students' digital literacy and 21st century skills.